(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
Following its colonial legal system, the criminal justice system in Nigeria has been focusing on punishing criminals since long with few considerations to the victims of the crimes. Consequently, the delay of examination and sometimes harassment or even extortion by the authorities may begin as victims often become exposed to so-called secondary victimization. The analysis in this work applies doctrinal legal research and literature review in analyzing the relevance of the concepts of victimology, restorative justice theory and international legal norms in informing victim support in Nigeria. The Paper examined Nigerian legislations (Criminal Code, Penal Code, Criminal Procedure Code, Administration of Criminal Justice Act 2015, etc.) in the light of international best experience. Findings revealed that though statutes facilitate the provision of discretionary compensation and restitution (e.g. ACJA 2015, EFCC Act s.14) enforcement is weak as the needs of victims are overruled. The scholarship observes that the retributive orientation left victims unrepaired through an inheritance in Nigeria. Victims are explicitly at the center of the restorative justice models (including the Nigerian Ehugbo). Globally, other instruments such as the UN declaration of the Victims (1985) and the ICC Rome Statute Article 75 support the right of the victims in relation to information, protection, participation, and reparation. My suggestion is that Nigeria should implement restorative practices and incorporate them into practice, as well as adopt the necessary mandatory schemes of victim compensation and update the laws with correspondent international standards in order to normalize the exploitation of the victim with the goal of providing him or her with justice and relief.